Late Cenozoic erosion rates in the Western Alps revealed by detrital apatite fission-track analysis - H.D. Sinclair; M. Naylor; L.A. Kirstein; A. Carter; S. Stanton; C. Glotzbach; M. Bernet; P.A. van der Beek (Earth and Planetary Science Letters, 2026)

Crash causation patterns and risk factors in Namibia: Through the lens of human behavioural risks - OR Ambunda; M Sinclair (Next Research, 2026)

How much Copper Do Calves Need? Retention and Hepatic Storage in Artificially Reared Milk-Fed Holstein–Friesian Calves - Amy P. Marsh; Liam A. Sinclair; Joe M. Roberts; Alexander M. Mackenzie; Stefan E. Yerby; James A. Huntington; James H. McCaughern (Biological Trace Element Research, 2026)
Excessive copper (Cu) absorption in calves may increase the risk of excessive hepatic Cu accumulation, likely driven by their elevated pre-ruminant absorptive capacity, with the potential for harmful Cu accumulation leading to adverse health and productivity outcomes. However, quantitative data across the weaning transition remains limited. This study utilized secondary data and bio-banked samples from 35 Holstein–Friesian bull calves to estimate hepatic Cu retention coefficients pre- and post-weaning. Although mean hepatic Cu concentrations remained broadly stable throughout the study, between 311 and 675 mg/kg of DM, changes varied by developmental stage: calves experienced hepatic Cu accumulation of 2.5 mg of Cu/kg of DM/d pre-weaning but a net reduction of 1.8 mg/kg of DM/d post-weaning. Pre-weaning calves exhibited a hepatic Cu retention coefficient of 81% compared to post-weaning calves, where the hepatic Cu retention coefficient was 5%. This reduction in absorptive capacity is consistent with increased rumen development and greater antagonism from dietary sulfur and molybdenum. Hepatic steady-state Cu intake requirements were estimated at 3 mg/kg of DM pre-weaning and 15 mg/kg of DM post-weaning. These findings demonstrate that the pre-weaning period represents a phase of high Cu retention and heightened susceptibility to hepatic Cu accumulation, even when dietary Cu meets current recommendations. Refining Cu feeding guidelines to more accurately reflect developmental stage and rumen maturation may help prevent excessive hepatic Cu loading while maintaining adequate mineral supply.

Multiple spatial scales and habitat composition drive wrasse distributions on the Great Barrier Reef - Carmen J. Ritter; Daniela M. Ceccarelli; Tane Sinclair-Taylor; Makeely I. Blandford; Andrew Cole; Murray Logan; Michael J. Emslie (Coral Reefs, 2026)

Substantial impacts from the 2024 summer reverse five years of coral cover gains on the Great Barrier Reef - Daniela M. Ceccarelli; Michael J. Emslie; Murray Logan; Peran Bray; Adriana R. Campili; Neal Cantin; Andrew Cole; Michelle J. Jonker; Tane H. Sinclair‑Taylor; Briony Stephenson (Coral Reefs, 2026)
Anthropogenic climate change is fuelling repeated marine heatwaves and has triggered the fourth global mass coral bleaching event in 2023–2025, causing widespread coral mortality worldwide. Here, we document the impacts of this event on the Great Barrier Reef (GBR), where heat accumulation peaked in February–March 2024 and caused mass coral bleaching for the seventh time since 1998. We use data from the Australian Institute of Marine Science (AIMS)’s Long-Term Monitoring Program (LTMP), which during the 2024–2025 season recorded coral cover on 124 reefs distributed across the full latitudinal and longitudinal extent of the GBR. Coral cover declined to 30.0% (26.6–33.8% Credible Intervals [CIs]; a 24.8% relative decline since 2024) in the Northern GBR, to 28.6% (25.7–31.6% CIs; a 14% relative decline) in the Central GBR and to 26.9% (23.1–30.9% CIs; a 30.6% relative decline) in the Southern GBR. For the Northern and Southern GBR, this was the largest single-year decline in hard coral cover since monitoring began in 1986. Acropora corals contributed between 40 and 80% of the increases and 48–70% of the decreases in hard coral cover over the 39 monitoring years. Despite the pivotal role Acropora play in accelerating post-disturbance recovery through their rapid growth, their vulnerability to disturbance also contributes to an increasingly volatile ecosystem, where hard coral cover oscillates between record lows and record highs. Climate change is already fuelling increasingly frequent and intense heatwaves, and conditions for reef recovery will continue to deteriorate without urgent reductions of greenhouse gas emissions.

New Zealand deep-sea black coral (Antipatharia) age and growth rates: Insights into early life growth patterns - Ashley N. Davis; Dianne M. Tracey; Erik Behrens; Stewart J. Fallon; John Hellstrom; Peter Marriott; Daniel J. Sinclair (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Environmental drivers and vulnerability of reef fishes highlight the need for multi-habitat conservation in remote insular ecosystems - Caio Ribeiro Pimentel; Ryan Andrades; Raphael M. Macieira; Hudson Tercio Pinheiro; Jean-Christophe Joyeux; Luiz Alves Rocha; Euan Sinclair Harvey; Tommaso Giarrizzo (Marine Environmental Research, 2026)

Using SEM to test the associations among women's childhood ecology, adult psychosocial life history traits, and mating effort - Lisa M. Bohon; Sophia Sinclair; Raquel R. Medeiros-Tejomaya; Jessica Hamel; Alexandra H.B. Hock (Evolution and Human Behavior, 2026)

Variegated decoupling: Australian firm strategies in the lithium global production network - Eli Hayes; Neil M. Coe; Lian Sinclair (The Extractive Industries and Society, 2025)

The Blue Carbon Cost Tool – understanding market potential and investment requirements for high-quality coastal wetland projects - Stefanie Simpson; Lindsey S. Smart; Emily Landis; Stephanie Van Laere; Abu S. M. G. Kibria; Olga Albot; Mark Beeston; Catherine E. Lovelock; Robert I. McDonald; Ryan P. Moyer; Thomas A. Worthington; Tania L. Maxwell; et al. (Frontiers in Marine Science, 2025)
Blue carbon ecosystems, such as mangroves, tidal marshes, and seagrasses, are important for climate mitigation. As carbon sinks, they often exhibit higher per hectare carbon storage capacity and sequestration rates than terrestrial systems. These ecosystems provide additional benefits, including enhancing water quality, sustaining biodiversity, and maintaining coastal resilience to climate change impacts. The widespread loss of blue carbon ecosystems due to anthropogenic activities can contribute to increasing carbon emissions globally. Monetizing blue carbon through carbon credits offers an avenue to generate revenue and incentivize conservation and restoration efforts. However, limited data on project costs and carbon benefits make prioritization of blue carbon projects challenging. To address these challenges, we have developed, in collaboration with blue carbon experts, the Blue Carbon Cost Tool. This is a user-friendly interface enabling comparison of three core market project components – 1) carbon credit estimation, 2) project cost estimation, and 3) a qualitative, non-economic feasibility assessment – to assess and compare potential for blue carbon projects. Tool simulations with data available from nine countries demonstrate (a) how factors such as country, ecosystem type and project scale drive variability, (b) the need for local or project-specific data to enhance accuracy and reduce uncertainty, particularly in tidal marsh and seagrass systems, and (c) that higher price tolerance or upfront capital is needed to bridge implementation and maintenance cost gaps. The Blue Carbon Cost Tool can aid project developers and investors to better understand market opportunity and the resources needed to develop high quality blue carbon market projects.

Anthropogenic climate change causes substantial loss of coral on the northern Great Barrier Reef during the 2024 bleaching event - Michael J. Emslie; Daniela M. Ceccarelli; Murray Logan; Makeely I. Blandford; Peran Bray; Adriana R. Campili; Neal Cantin; Severine Choukroun; Andrew Cole; Michelle J. Jonker; Clothilde Langlais; Marji Puotinen; et al. (Coral Reefs, 2025)

The discovery of a genetically distinct subpopulation of Haast tokoeka (Southern brown kiwi, Apteryx australis ‘Haast’) - Talia Brav-Cubitt; Heath M. Sinclair; Hugh A. Robertson; Andrew J. Veale (Conservation Genetics, 2025)
The Haast tokoeka ( Apteryx australis ‘Haast’) is a threatened evolutionarily significant unit (ESU) of tokoeka or southern brown kiwi in Aotearoa New Zealand. In this study, we investigated the genetic relationships of a small newly discovered population of tokoeka located at Junction Hill near Haast, which is geographically isolated from other tokoeka populations. Using pin feathers collected from five individuals at Junction Hill, we analysed 15 microsatellite loci and 1283 base pairs from two mitochondrial DNA loci (control region and cytochrome b ( Cytb )) to compare our results with those previously generated for Haast ( n = 49), northern Fiordland ( n = 7), southern Fiordland ( n = 4), and Rakiura ( n = 12) tokoeka. Our results show that the Junction Hill individuals are Haast tokoeka, but display genetic differentiation in Principle Component Analysis (PCA) and genetic assignment plots from the nearest Haast tokoeka population 18 km away in the Upper Arawhata Valley. The five Junction Hill individuals all possess a unique mitochondrial DNA haplotype that has not been observed previously. The mean allelic richness of the Junction Hill population (1.82) was slightly lower compared to the main Haast population (2.13). The presence of the Junction Hill population provides both numerical and range increases for the Haast tokoeka, and potentially contributes valuable new genetic diversity to the taxon. Further monitoring and conservation actions, such as increased pest control and translocations, may be necessary to ensure the preservation of this population and its unique genetic traits.

Fission‐Fusion Group Dynamics and Cooperative Hunting Stabilise Social Carnivore Populations - J. M. Fryxell; S. Mduma; J. Masoy; J. Grant C. Hopcraft; A. R. E. Sinclair; R. Dejeante; C. Packer (Ecology Letters, 2025)
Theory suggests that large social groups of carnivores should be unsustainable, due to reduced foraging efficiency because of overlapping perception radii. Using Serengeti lions as a case study, we apply behaviourally based foraging models to show that fragmentation of social groups into smaller subgroups or mutual cooperation during hunting are both plausible hypothetical mechanisms capable of sustaining larger lion prides. Data from the Serengeti ecosystem demonstrate that lion prides typically fragment into small hunting groups that are well approximated by an exponential distribution of group sizes typical of fission‐fusion social systems. A model linking fission‐fusion group dynamics with predator–prey interaction predicts both the surprising degree of population stability of the Serengeti lions as well as the long‐term persistence of large prides. There is little evidence, however, that Serengeti lions cooperate during hunting except when they hunt Cape buffalo, so fission‐fusion is apparently the dominant stabilising process in Serengeti.

Effects of acclimation on the cold tolerance of the pepper weevil - D. Catalina Fernández; Sherah L. VanLaerhoven; Brent J. Sinclair; Roselyne M. Labbé (Journal of Pest Science, 2025)
The pepper weevil, Anthonomus eugenii , is a subtropical pest of pepper plants that appears to be expanding its geographic range as evidenced by its increasing occurrence and persistence in field and greenhouse pepper crops in temperate areas. Here, we investigated the cold tolerance of A. eugenii and its potential for winter survival in temperate areas by comparing non-acclimated (24 °C) and cold acclimated (10 °C) adults and larvae for their cold tolerance strategy, supercooling points, and lower lethal thermal limits. Acclimated larvae were treated with silver iodide to assess their survival in the presence of an ice nucleator. Survival of non-acclimated adults was measured following exposure to 0 °C for an extended period. We also tested whether non-acclimated adults and larvae could survive winter at three outdoor sites in southwestern Ontario (agricultural field, adjacent to unheated building, and inside an unheated building). Adults and larvae died at freezing and even pre-freezing temperatures. Acclimation improved adult cold tolerance, decreasing the LT 50 by 3 °C, with half of the non-acclimated adults surviving around 6 days at 0 °C. External inoculation increased larval supercooling points (SCPs), but did not improve cold tolerance. In winter field studies, survival was evident only in the first month, but no insect survived afterwards at any of the overwintering sites. We conclude that A. eugenii is chill-susceptible, and winter temperatures will restrict outdoor establishment in temperate areas, but that high winter temperatures in empty greenhouses encourage indoor establishment.

A record of the transition from foreland to piggy-back basin from the western Churia Range in Central Nepal: Evidence from luminescence dating and geomorphology - Donny R. Wahyudi; Hugh D. Sinclair; Simon M. Mudd; Rachel K. Smedley; Emma L.S. Graf (Geomorphology, 2025)

A Re-evaluation of the Optimal Liver Copper Concentrations for Health, Performance and Fertility of Replacement Holstein–Friesian Heifers - Amy P. Marsh; Liam A. Sinclair; Joe M. Roberts; Alexander M. Mackenzie; James H. McCaughern (Biological Trace Element Research, 2025)

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Spatial Variation in Upper Limits of Coral Cover on the Great Barrier Reef - Mariana Álvarez‐Noriega; Juan C. Ortiz; Daniela M. Ceccarelli; Michael J. Emslie; Katharina E. Fabricius; Michelle J. Jonker; Marji Puotinen; Barbara J. Robson; Chris M. Roelfsema; Tane H. Sinclair‐Taylor; Renata Ferrari (Global Ecology and Biogeography, 2024)
Aim Identifying the maximum coral cover that a coral community can sustain (i.e., its ‘upper limit’) is important for predicting community dynamics and improving management strategies. Here, we quantify the relationship between estimated upper limits and key environmental factors on coral reefs: hard substrate availability, temperature and water clarity. Location Great Barrier Reef (GBR), Australia (over 1400 km). Time Period 1990 to 2022. Major Taxa Studied Scleractinian corals. Methods We used 32 years of data on coral cover around reef perimeters. Each reef was divided into four wave‐exposure habitats depending on prevailing wind conditions. For each site, we determined if hard coral cover had reached a plateau or upper limit. Next, we extracted existing estimates of hard substrate availability, modelled water temperature and Secchi depth. Then, we quantified the relationship between these environmental variables and the upper limits. Results We found varying upper limits across the GBR, with a median of 33% coral cover and only 17% of the estimated upper limits exceeded 50% coral cover. Upper limits increased towards the southern reefs. Our results show that upper limits increased with increasing hard substrate availability and decreased with temperature and, to a lesser extent, with water clarity. Main Conclusions The upper limits estimated in this study are much lower than what is commonly assumed when modelling ecological dynamics, most likely resulting in predicted recovery rates being inappropriately high. Although hard substrate ultimately restricted upper limits, there are mechanisms constraining the proportion of hard substrate that is covered by hard corals. The negative relationship between temperature and upper limits cannot be explained by changes in macroalgal abundance but may be related to changes in species composition. The quantitative relationships between the upper limits of coral cover and environmental variables will provide critical information to prioritise sites for management interventions.

Regional‐scale disturbances drive long‐term decline of inshore coral reef fish assemblages in the Great Barrier Reef Marine Park - Daniela M. Ceccarelli; Murray Logan; Richard D. Evans; Geoffrey P. Jones; Marji Puotinen; Caroline Petus; Garry R. Russ; Tane Sinclair‐Taylor; Maya Srinivasan; David H. Williamson (Global Change Biology, 2024)
Anthropogenic pressure is increasing the variety and frequency of environmental disturbance events, limiting recovery and leading to long‐term declines in wild plant and animal populations. Coral reefs and associated fish assemblages are inherently dynamic due to their susceptibility to a host of disturbances, but regional‐scale nuances in the drivers of long‐term change frequently remain poorly resolved. Here, we examine the effects of multiple potential drivers of change in coral reef fish assemblages across 4 inshore regions of the Great Barrier Reef Marine Park (GBRMP), Australia, over 12–14 years (2007–2021). Each region had a unique disturbance history, in conjunction with long‐term changes in physical and habitat variables. Phases of recovery were apparent in the years between disturbance events at all locations, but these were not long enough to prevent substantial declines in reef fish density (by 33%–72%) and species richness (by 41%–75%) throughout the study period. The main drivers of change in fish assemblages varied among regions; however, the most rapid changes followed cyclone and flood events. Limited recovery periods resulted in temporal shifts in fish species composition from typically coral‐associated to algae‐associated. Most trophic groups declined in density except farmers, grazers, omnivores and parrotfish. No‐take marine reserves (NTMRs) had small and inconsistent effects on total fish assemblages, but delivered benefits for fishery‐targeted piscivores. Our findings suggest that coral reef responses to local stressors and cumulative escalating climate change impacts are highly variable at regional scales, and that small NTMRs are unlikely to mitigate the impacts of increasingly frequent climatic disturbances. Nearshore coral reefs worldwide are high‐value habitats that are either already degraded or vulnerable to degradation and the loss of important fish groups. Global efforts to reduce greenhouse gas emissions must be coupled with effective local management that can support the functioning and adaptive capacity of coral reefs.

Exposure to PFAS contaminated urban wetland water causes similar metabolic alterations to laboratory-based exposures in the freshwater amphipod Austrochiltonia subtenuis - Georgia M. Sinclair; Oliver A.H. Jones; Navneet Singh; Sara M. Long (Environmental Toxicology and Pharmacology, 2024)

Changing dynamics of Great Barrier Reef hard coral cover in the Anthropocene - Michael J. Emslie; Daniela M. Ceccarelli; Murray Logan; Makeely I. Blandford; Peran Bray; Adriana Campili; Michelle J. Jonker; Joshua G. Parker; Tara Prenzlau; Tane H. Sinclair-Taylor (Coral Reefs, 2024)

Critical mineral strategies in Australia: Industrial upgrading without environmental or social upgrading - Lian Sinclair; Neil M. Coe (Resources Policy, 2024)

Late Cretaceous-Eocene exhumation of the northern Lhasa terrane and topographic implications for the Central Tibet - Gaoyuan Sun; Hugh D. Sinclair; Cristina Persano; Finlay M. Stuart; Xiumian Hu (Lithos, 2024)

Economic values for ecosystem services: A global synthesis and way forward - L.M. Brander; R. de Groot; J.P. Schägner; V. Guisado-Goñi; V. van 't Hoff; S. Solomonides; A. McVittie; F. Eppink; M. Sposato; L. Do; A. Ghermandi; M. Sinclair; et al. (Ecosystem Services, 2024)

Spatial variation in the sensitivity of freshwater macroinvertebrate assemblages to chemical stressors - Ruoyu Liang; Thomas M. Sinclair; Peter S. Craig; Lorraine Maltby (Water Research, 2024)

Developmental programming: Impact of preconceptional and gestational exposure to a real-life environmental chemical mixture on maternal steroid, cytokine and oxidative stress milieus in sheep - S.V. Thangaraj; L. Zeng; S. Pennathur; R. Lea; K.D. Sinclair; M. Bellingham; N.P. Evans; R. Auchus; V. Padmanabhan (Science of The Total Environment, 2023)

Impostor Phenomenon and Grit as Predictors of Job Satisfaction in Female Pharmacy Faculty - Lilia Z. Macias-Moriarity; Starlette M. Sinclair; Doretha Walker; Miriam Purnell (Pharmaceutical Research, 2023)

Evaluating the influence of nature connection and values on conservation attitudes at a tropical deforestation frontier - Katarzyna M. Mikołajczak; Jos Barlow; Alexander C. Lees; Christopher D. Ives; Micha Strack; Oriana Trindade de Almeida; Agnis C. Souza; Frazer Sinclair; Luke Parry (Conservation Biology, 2023)
Inner phenomena, such as personal motivations for pursuing sustainability, may be critical levers for improving conservation outcomes. Most conservation research and policies, however, focus on external phenomena (e.g., ecological change or economic processes). We explored the factors shaping 9 conservation attitudes toward forest and wildlife protection among colonist farmers around an Amazonian deforestation frontier. Our data comprised 241 face‐to‐face quantitative surveys, complemented with qualitative insights from open‐ended questionnaire responses and opportunistic semistructured interviews. To account for the full spectrum of possible inner motivations, we employed measures of nature connection (indicating biospheric motivation) and personal values organized around the traditionalism (traditionalist through to high openness to change) and universalism dimensions (egoistic through to altruistic motivations). We used averaged beta‐binomial generalized linear models to assess the role of external factors (socioeconomic, sociodemographic, and environmental) and personal (inner) motivations on the variation in attitudes. Each attitude was modeled separately. The relative importance of each predictor was judged by the proportion of models where it appeared as significant. Proconservation views were expressed by the majority (at least 65%) of the respondents in 7 out of the 9 attitude models. The most consistent predictors were emotional nature connection and personal values (significant in 4–6 out of 9 models), rather than external phenomena (significant in 0–5 models). However, the poorest farmers had lower scores on the agreement with prioritizing nature over development (𝛽 = –0.52, 95% CI: –0.96 to –0.07). Qualitative data also indicated that economic barriers hinder forest conservation on farms. These results suggest that biospheric, traditionalistic, and altruistic motivations promote people's proconservation attitudes, but nurturing these latent motivations is unlikely to improve conservation outcomes if material poverty remains unaddressed. Integrating the inner–outer perspective into conservation thinking and practical interventions could foster environmental stewardship and increase human well‐being.

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Recent advances in the delivery and applications of nonviral CRISPR/Cas9 gene editing - Frazer Sinclair; Anjuman A. Begum; Charles C. Dai; Istvan Toth; Peter M. Moyle (Drug Delivery and Translational Research, 2023)

A retrospective analysis of mid-infrared observations of the Comet D/Shoemaker-Levy 9 and Wesley impacts on Jupiter - J.A. Sinclair; C.M. Lisse; G.S. Orton; M. Krishnamoorthy; L.N. Fletcher; J. Hora; C. Palotai; T. Hayward (Icarus, 2023)

Changes in metabolic profiles of amphipods Allorchestes compressa after acute exposures to copper, pyrene, and their mixtures - Hao Shen; Damien Nzabanita; Georgia M. Sinclair; Hung Vu; Stephen Grist; Dayanthi Nugegoda; Sara M. Long (Environmental Toxicology and Pharmacology, 2023)

Developmental programming: Preconceptional and gestational exposure of sheep to a real-life environmental chemical mixture alters maternal metabolome in a fetal sex-specific manner - S.V. Thangaraj; M. Kachman; K.M. Halloran; K.D. Sinclair; R. Lea; M. Bellingham; N.P. Evans; V. Padmanabhan (Science of The Total Environment, 2023)

Saturn’s seasonal variability from four decades of ground-based mid-infrared observations - James S.D. Blake; L.N. Fletcher; G.S. Orton; A. Antuñano; M.T. Roman; Y. Kasaba; T. Fujiyoshi; H. Melin; D. Bardet; J.A. Sinclair; M. Es-Sayeh (Icarus, 2023)

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

Is substrate choice an overlooked variable in ecotoxicology experiments? - Georgia M. Sinclair; Michela Di Giannantonio; Oliver A. H. Jones; Sara M. Long (Environmental Monitoring and Assessment, 2023)
It is crucial to understand the effects caused by experimental parameters such as temperature, light, and food type on lab and field-based ecotoxicology experiments, as these variables, and combinations thereof, can affect results. The type of substrate used in exposure experiments, however, is generally assumed to have no effect. This may not always be correct. The metabolic changes in the freshwater crustacean, Austrochiltonia subtenuis exposed to copper, using three common substrates, gauze; toilet paper; and cellulose were investigated. Substrate alone did not affect survival, but each substrate elicited a different metabolic response and adult and juvenile amphipods had different substrate preferences. Several classes of metabolites were shown to change in response to different substrates and toxicant. These included disaccharides, monosaccharides, fatty acids, and tricarboxylic acid cycle intermediates. The results illustrate that metabolomic responses can differ in response to experimental factors that were previously thought not to be significant. In fact, our data indicate that substrate should be viewed as an experimental factor as important to control for as more well-known confounders such as temperature or food, thus challenging the current paradigm. Assuming substrate type has no effect on the experiment could potentially lead to errors in contaminant toxicity assessments. We propose that ideal good practise would be that all experimental factors should be evaluated for their potential influence on metabolomic profiles prior to contaminant response experiments being undertaken.

Are stormwater detention ponds protecting urban aquatic ecosystems? a case study using depressional wetlands - Kayla M. Hess; James S. Sinclair; Alexander J. Reisinger; Eban Z. Bean; Basil V Iannone III (Urban Ecosystems, 2022)

The effects of nest location and beach environment on hatching success for leatherback (Dermochelys coriacea) and green (Chelonia mydas) sea turtles on Bioko Island, Equatorial Guinea - Callie A. Veelenturf; Elizabeth M. Sinclair; Peter Leopold; Frank V. Paladino; Shaya Honarvar (Marine Biology, 2022)

A recessive variant in TFAM causes mtDNA depletion associated with primary ovarian insufficiency, seizures, intellectual disability and hearing loss - Farid Ullah; Waqar Rauf; Kamal Khan; Sheraz Khan; Katrina M. Bell; Vanessa Cristina de Oliveira; Muhammad Tariq; Shabnam Bakhshalizadeh; Philippe Touraine; Nicholas Katsanis; Andrew Sinclair; Sijie He; et al. (Human Genetics, 2021)

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Functional traits reveal the dominant drivers of long‐term community change across a North American Great Lake - James S. Sinclair; Michael E. Fraker; James M. Hood; Kenneth T. Frank; Mark R. DuFour; Ann Marie Gorman; Stuart A. Ludsin (Global Change Biology, 2021)
Ecosystems worldwide have been impacted by multiple anthropogenic stressors, yet efforts to understand and manage these impacts have been hindered by difficulties in disentangling relative stressor effects. Theoretically, the actions of individual stressors can be delineated based on associated changes in functional traits and these relationships should be generalizable across communities comprised of different species. Thus, combining trait perspectives with community composition data could help to identify the relative influence of different stressors. We evaluated the utility of this combined approach by quantifying shifts in fish species and trait composition in Lake Erie during the past 50 years (1969–2018) in relation to human‐driven changes in nutrient inputs, climate warming, and biological invasions. Species and trait shifts were also compared between two Lake Erie basins, which differ in their environmental and biological characteristics, to identify trait responses that were generalizable across different ecosystems versus those that were context dependent. Our analyses revealed consistent species changes across basins, and shifts in feeding and thermal traits, that were primarily associated with altered nutrient inputs (oligotrophication followed by eutrophication). We found no or inconsistent trait‐based evidence for the effects of warming and two invasive fishes. Context‐dependent trait responses were also evident; nutrient inputs were related to shifts in species tolerant of turbidity in the shallow, eutrophic western basin, which contrasted to shifts between benthopelagic and benthic species in the deeper central basin. Our results reveal the dominant effects of specific stressors on a large freshwater lake and offer a framework for combining species‐based and trait‐based approaches to delineate the impacts of simultaneous stressors on communities of perturbed natural ecosystems.

Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

Regional versus latitudinal variation in the life‐history traits and demographic rates of a reef fish, Centropyge bispinosa , in the Coral Sea and Great Barrier Reef Marine Parks, Australia - Jake R. Lowe; Samuel D. Payet; Hugo B. Harrison; Jean‐Paul A. Hobbs; Andrew S. Hoey; Brett M. Taylor; Tane H. Sinclair‐Taylor; Morgan S. Pratchett (Journal of Fish Biology, 2021)
Environmental temperature is an important determinant of physiological processes and life histories in ectotherms. Over latitudinal scales, variation in temperature has been linked to changes in life‐history traits and demographic rates, with growth and mortality rates generally being greatest at low latitudes, and longevity and maximum length being greater at higher latitudes. Using the two‐spined angelfish, Centropyge bispinosa , as our focal species, we compared growth patterns, growth rates, longevity, mortality, asymptotic length and maximum length across 22 reefs that span 13° of latitude within the Great Barrier Reef Marine Park (GBRMP) and the Coral Sea Marine Park (CSMP), Australia. We found no predictable latitudinal variation in mortality rates, growth patterns, growth rates, asymptotic or maximum length of C. bispinosa at regional to biogeographic scales. However, C. bispinosa consistently exhibited reduced longevity at lower, warmer latitudes within the CSMP. The greatest differences in mean maximum length of C. bispinosa were between continental (GBRMP) and oceanic (central CSMP) reefs of similar latitude, with individuals being larger on average on continental versus oceanic reefs. The lack of predictable life‐history and demographic variation in C. bispinosa across a 13° latitudinal gradient within the CSMP, coupled with differences in mean maximum length between continental and oceanic reefs at similar latitudes, suggest that local environmental conditions have a greater influence than environmental temperature on the demographic rates and life‐history traits of C. bispinosa .

Farmer-led approaches to increasing tree diversity in fields and farmed landscapes in Ethiopia - Abayneh Derero; Richard Coe; Catherine Muthuri; Kiros M. Hadgu; Fergus Sinclair (Agroforestry Systems, 2021)
Increasing tree cover and managing trees better on farms in Ethiopia supports livelihoods and the environment but most tree-planting schemes promote only a few species. This research aimed to understand farmers’ tree planting priorities in Oromia, Ethiopia and address challenges involved in meeting them. Tree species and planting niches were elicited through focus group discussions. Participatory trials compared 17 tree species across seven on-farm planting niches and seedling survival and growth patterns were evaluated. Farmers suggested a high diversity of tree species suitable for each niche with fruit species mainly selected for homesteads. The diversity of desired tree species is much higher than that typically available in nurseries or promoted by tree planting projects. Meeting planting demands was difficult because the existing seedling supply does not support diversity. Evaluation of tree survival showed striking differences among species, farms, agroecologies and planting niches. There was high variation in seedling survival amongst the tree species planted on 1893 farm/planting niche locations, indicating impact of local level risk factors attributable to management, biotic and abiotic causes. Growth differences of the six shared species common to both agroecologies across different niches, showed that the effects of species and niche were significant on growth. A farmer-led approach to increasing tree cover that couples understanding of species and planting niche preferences with appropriate seedling supply and management is proposed as a means to increase the diversity of trees in farmed landscapes.

Growth patterns of specialized reef fishes distributed across the Red Sea to Gulf of Aden - Joseph D. DiBattista; Brett M. Taylor; Jean-Paul A. Hobbs; Tane H. Sinclair-Taylor; Darren J. Coker; Elizabeth D. L. Trip; J. Howard Choat; Diego Lozano-Cortés; Nora M. Kandler; Michael L. Berumen (Environmental Biology of Fishes, 2021)

Inspection of a Restricted Access Site Using UAV Perimeter Survey with the ARDUO Direction-Capable Gamma Spectrometer - Laurel E. Sinclair; Carolyn M. Chen (Pure and Applied Geophysics, 2021)

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Blue Restoration – Building Confidence and Overcoming Barriers - Phoebe J. Stewart-Sinclair; Jemma Purandare; Elisa Bayraktarov; Nathan Waltham; Simon Reeves; John Statton; Elizabeth A. Sinclair; Benjamin M. Brown; Zoë I. Shribman; Catherine E. Lovelock (Frontiers in Marine Science, 2020)

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Determining critical inter-nesting, migratory, and foraging habitats for the conservation of East Atlantic green turtles (Chelonia mydas) - Emily K. Mettler; Chelsea E. Clyde-Brockway; Elizabeth M. Sinclair; Frank V. Paladino; Shaya Honarvar (Marine Biology, 2020)

Process Monitoring of Moisture Content and Mass Transfer Rate in a Fluidised Bed with a Low Cost Inline MEMS NIR Sensor - Claudio R. Avila; Joan Ferré; Rodrigo Rocha de Oliveira; Anna de Juan; Wayne E. Sinclair; Faiz M. Mahdi; Ali Hassanpour; Timothy N. Hunter; Richard A. Bourne; Frans L. Muller (Pharmaceutical Research, 2020)
Purpose The current trend for continuous drug product manufacturing requires new, affordable process analytical techniques (PAT) to ensure control of processing. This work evaluates whether property models based on spectral data from recent Fabry–Pérot Interferometer based NIR sensors can generate a high-resolution moisture signal suitable for process control. Methods Spectral data and offline moisture content were recorded for 14 fluid bed dryer batches of pharmaceutical granules. A PLS moisture model was constructed resulting in a high resolution moisture signal, used to demonstrate (i) endpoint determination and (ii) evaluation of mass transfer performance. Results The sensors appear robust with respect to vibration and ambient temperature changes, and the accuracy of water content predictions (±13 % ) is similar to those reported for high specification NIR sensors. Fusion of temperature and moisture content signal allowed monitoring of water transport rates in the fluidised bed and highlighted the importance water transport within the solid phase at low moisture levels. The NIR data was also successfully used with PCA-based MSPC models for endpoint detection. Conclusions The spectral quality of the small form factor NIR sensor and its robustness is clearly sufficient for the construction and application of PLS models as well as PCA-based MSPC moisture models. The resulting high resolution moisture content signal was successfully used for endpoint detection and monitoring the mass transfer rate.

Does Proximity to Wetlands Matter? A Landscape-Level Analysis of the Influence of Local Wetlands on the Public’s Concern for Ecosystem Services and Conservation Involvement - Emily J. Wilkins; Wilson Sinclair; Holly M. Miller; Rudy M. Schuster (Wetlands, 2019)

Thermal limits of summer-collected Pardosa wolf spiders (Araneae: Lycosidae) from the Yukon Territory (Canada) and Greenland - Susan E. Anthony; Christopher M. Buddle; Toke T. Høye; Brent J. Sinclair (Polar Biology, 2019)

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

How does high DHA fish oil affect health? A systematic review of evidence - Samaneh Ghasemi Fard; Fenglei Wang; Andrew J. Sinclair; Glenn Elliott; Giovanni M. Turchini (Critical Reviews in Food Science and Nutrition, 2019)

Seeds in motion: Genetic assignment and hydrodynamic models demonstrate concordant patterns of seagrass dispersal - Elizabeth A. Sinclair; Leonardo Ruiz‐Montoya; Siegfried L. Krauss; Janet M. Anthony; Renae K. Hovey; Ryan J. Lowe; Gary A. Kendrick (Molecular Ecology, 2018)
Movement is fundamental to the ecology and evolutionary dynamics within species. Understanding movement through seed dispersal in the marine environment can be difficult due to the high spatial and temporal variability of ocean currents. We employed a mutually enriching approach of population genetic assignment procedures and dispersal predictions from a hydrodynamic model to overcome this difficulty and quantify the movement of dispersing floating fruit of the temperate seagrass Posidonia australis Hook.f. across coastal waters in south‐western Australia. Dispersing fruit cohorts were collected from the water surface over two consecutive years, and seeds were genotyped using microsatellite DNA markers. Likelihood‐based genetic assignment tests were used to infer the meadow of origin for seed cohorts and individuals. A three‐dimensional hydrodynamic model was coupled with a particle transport model to simulate the movement of fruit at the water surface. Floating fruit cohorts were mainly assigned genetically to the nearest meadow, but significant genetic differentiation between cohort and most likely meadow of origin suggested a mixed origin. This was confirmed by genetic assignment of individual seeds from the same cohort to multiple meadows. The hydrodynamic model predicted 60% of fruit dispersed within 20 km, but that fruit was physically capable of dispersing beyond the study region. Concordance between these two independent measures of dispersal provides insight into the role of physical transport for long distance dispersal of fruit and the consequences for spatial genetic structuring of seagrass meadows.

The limitations of some European healthcare databases for monitoring the effectiveness of pregnancy prevention programmes as risk minimisation measures - R. A. Charlton; V. Bettoli; H. J. Bos; A. Engeland; E. Garne; R. Gini; A. V. Hansen; L. T. W. de Jong-van den berg; S. Jordan; K. Klungsøyr; A. J. Neville; A. Pierini; et al. (European Journal of Clinical Pharmacology, 2018)

Character and origin of De Geer moraines in the Seacoast region of New Hampshire, USA - Samantha N. Sinclair; Joseph M. Licciardi; Seth W. Campbell; Brian M. Madore (Journal of Quaternary Science, 2018)
Previously unrecognized clusters of regularly spaced, low‐relief ridges were recently revealed by LiDAR data acquired in the Seacoast region of New Hampshire, USA. Based on their morphometry and geologic context, these features are interpreted as De Geer moraines that formed during regional deglaciation. While De Geer moraines are widely recognized as products of ice recession in glaciomarine settings, their formative processes remain debated. Here, we integrate geospatial mapping, morphometric analyses, stratigraphic investigations and ground‐penetrating radar (GPR) subsurface profiling to characterize De Geer moraines in New Hampshire and assess their origin. On average, the moraines are 1.2 km long, 28 m wide, 1.7 m tall and spaced 104 m apart. Trenches expose stratigraphic units consistent with subaqueous deposition along a tidewater glacier margin, including subglacial traction till indicative of proglacial pushing, and gravity‐driven flow deposits on an ice‐distal moraine slope. GPR profiles reveal variable till thicknesses beneath the ridges and stratified sediment in adjacent swales. Our findings suggest De Geer moraine formation was driven by annual oscillations of the retreating Laurentide Ice Sheet margin. In this interpretation, average moraine spacing would represent a retreat rate of ∼100 m a −1 , which is in line with previous estimates of recession rates across New England.

Mutations in KIAA0753 cause Joubert syndrome associated with growth hormone deficiency - Joshi Stephen; Thierry Vilboux; Luhe Mian; Chulaluck Kuptanon; Courtney M. Sinclair; Deniz Yildirimli; Dawn M. Maynard; Joy Bryant; Roxanne Fischer; Meghana Vemulapalli; James C. Mullikin; Marjan Huizing; et al. (Human Genetics, 2017)

Microbial changes linked to the accelerated degradation of the herbicide atrazine in a range of temperate soils - R. L. Yale; M. Sapp; C. J. Sinclair; J. W. B. Moir (Environmental Science and Pollution Research, 2017)

Genetic signatures of Bassian glacial refugia and contemporary connectivity in a marine foundation species - Elizabeth A. Sinclair; Janet M. Anthony; Dougal Greer; Leonardo Ruiz‐Montoya; Suzanna M. Evans; Siegfried L. Krauss; Gary A. Kendrick (Journal of Biogeography, 2016)
Aim To examine the population genetic structure in Posidonia australis meadows , a marine foundation species capable of long distance dispersal ( LDD ), and the role of historical versus contemporary processes in shaping post Last Glacial Maximum ( LGM ) re‐colonization. Location Southeastern Australia including the Bass Strait Islands. Methods We generated multilocus genotypes and assessed spatial patterns of genetic diversity. Relationships among meadows were assessed in terms of historical sea level changes, oceanic boundary currents and contemporary seed dispersal based on a hydrodynamic model. Results There was strong regional spatial genetic structuring among P. australis meadows in south‐eastern Australia, which was congruent with three recognized marine biogeographical provinces [Peronian (eastern), Flindersian (western and southern), and Maugean (south‐eastern)]. The genetic data suggest Maugean meadows persisted in isolation during the LGM , with evidence for admixture and contemporary gene flow. Simulated dispersal events identified high rates of local and regional demographic connectivity, with evidence for occasional LDD events. Main conclusions The strong regional differentiation is consistent with long‐term barriers to dispersal persisting in the marine environment through many sea level fluctuations. Bass Strait Island meadows all have strong signals of genetic admixture. A weak but significant isolation by distance relationship is consistent with a historical signal and contemporary seed dispersal mostly within the Bass Strait.

Thermal biology and immersion tolerance of the Beringian pseudoscorpion Wyochernes asiaticus - Susan E. Anthony; Christopher M. Buddle; Brent J. Sinclair (Polar Biology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

A unified gene catalog for the laboratory mouse reference genome - Y. Zhu; J. E. Richardson; P. Hale; R. M. Baldarelli; D. J. Reed; J. M. Recla; R. Sinclair; T. B. K. Reddy; C. J. Bult (Mammalian Genome, 2015)

Farmers in Côte d’Ivoire value integrating tree diversity in cocoa for the provision of ecosystem services - E. Smith Dumont; G. M. Gnahoua; L. Ohouo; F. L. Sinclair; P. Vaast (Agroforestry Systems, 2014)

Learning for Sustainability Among Faith-Based Organizations in Kenya - Joanne M. Moyer; A. John Sinclair; Alan P. Diduck (Environmental Management, 2014)

Genetic diversity in threatened Posidonia australis seagrass meadows - Suzanna M. Evans; Elizabeth A. Sinclair; Alistair G. B. Poore; Peter D. Steinberg; Gary A. Kendrick; Adriana Vergés (Conservation Genetics, 2014)

Impacts of stress and sex hormones on dopamine neurotransmission in the adolescent brain - Duncan Sinclair; Tertia D Purves-Tyson; Katherine M Allen; Cynthia Shannon Weickert (Psychopharmacology, 2014)

Chemosensory and thermal cue responses in the sub-Antarctic moth Pringleophaga marioni: Do caterpillars choose Wandering Albatross nest proxies? - Tanya M. Haupt; Brent J. Sinclair; Steven L. Chown (Polar Biology, 2014)

Multi-Scale Parameterisation of a Myocardial Perfusion Model Using Whole-Organ Arterial Networks - Eoin R. Hyde; Andrew N. Cookson; Jack Lee; Christian Michler; Ayush Goyal; Taha Sochi; Radomir Chabiniok; Matthew Sinclair; David A. Nordsletten; Jos Spaan; Jeroen P. H. M. van den Wijngaard; Maria Siebes; et al. (Annals of Biomedical Engineering, 2014)

Physiological properties of a drought-resistant wild soybean genotype: Transpiration control with soil drying and expression of root morphology - Thomas M. Seversike; Shannon M. Sermons; Thomas R. Sinclair; Thomas E. Carter; Thomas W. Rufty (Plant and Soil, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Neuronal sirtuin1 mediates retinal vascular regeneration in oxygen-induced ischemic retinopathy - Jing Chen; Shaday Michan; Aimee M. Juan; Christian G. Hurst; Colman J. Hatton; Dorothy T. Pei; Jean-Sebastien Joyal; Lucy P. Evans; Zhenghao Cui; Andreas Stahl; Przemyslaw Sapieha; David A. Sinclair; et al. (Angiogenesis, 2013)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Comparison of common bean (Phaseolus vulgaris L.) genotypes for nitrogen fixation tolerance to soil drying - Mura Jyostna Devi; Thomas R. Sinclair; Stephen E. Beebe; Idupulapati M. Rao (Plant and Soil, 2013)

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Jumping on the Omega-3 Bandwagon: Distinguishing the Role of Long-Chain and Short-Chain Omega-3 Fatty Acids - Giovanni M. Turchini; Peter D. Nichols; Colin Barrow; Andrew J. Sinclair (Critical Reviews in Food Science and Nutrition, 2012)

Thermal biology of the alien ground beetle Merizodus soledadinus introduced to the Kerguelen Islands - L. Lalouette; C. M. Williams; M. Cottin; B. J. Sinclair; D. Renault (Polar Biology, 2012)

Effects of light environment on maize in hillside agroforestry systems of Nepal - Thakur Prasad Tiwari; Robert M. Brook; Paul Wagstaff; Fergus L. Sinclair (Food Security, 2012)

Temporal and spatial variation in the δ15N and δ13C values of fish and squid from Alaskan waters - Carolyn M. Kurle; Elizabeth H. Sinclair; Ann E. Edwards; Carolyn J. Gudmundson (Marine Biology, 2011)

Characterisation of polymorphic microsatellite markers isolated from Drakaea glyptodon Fitz. (Orchidaceae) - J. M. Anthony; R. D. Phillips; E. A. Sinclair; K. W. Dixon (Conservation Genetics Resources, 2010)

Genotypic variability among peanut (Arachis hypogea L.) in sensitivity of nitrogen fixation to soil drying - M. Jyostna Devi; Thomas R. Sinclair; Vincent Vadez (Plant and Soil, 2010)

Characterisation of polymorphic microsatellite markers in the widespread Australian seagrass, Posidonia australis Hook. f. (Posidoniaceae), with cross-amplification in the sympatric P. sinuosa - E. A. Sinclair; J. Anthony; G. T. Coupland; M. Waycott; M. D. Barrett; R. L. Barrett; M. L. Cambridge; M. J. Wallace; K. W. Dixon; S. L. Krauss; G. A. Kendrick (Conservation Genetics Resources, 2009)

A 3D modeling method to calculate the surface areas of coral branches - A. M. Jones; N. E. Cantin; R. Berkelmans; B. Sinclair; A. P. Negri (Coral Reefs, 2008)

Losing ‘Nemo’: bleaching and collection appear to reduce inshore populations of anemonefishes - A. M. Jones; S. Gardner; W. Sinclair (Journal of Fish Biology, 2008)
Surveys of anemonefishes (Amphiprioninae) were conducted on reefs in two regions of the Great Barrier Reef Marine Park with contrasting histories of disturbance to determine the degree to which spatial variation might be explained by bleaching or management status. Densities of anemonefishes were lower on reefs in the bleaching‐impacted Keppel Islands than on reefs in Far North Queensland. No anemonefishes or anemones were found on or near bleached corals in the Keppel Islands. Furthermore, the highest densities of fishes were found on reefs closed to fishing and aquarium collecting in both the Keppel Islands and Far North Queensland, which suggests that collecting is compounding the effects of bleaching. These results emphasize the importance of understanding the interaction between bleaching events and anthropogenic disturbance upon commercially exploited species.

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Long‐Term Ecosystem Dynamics in the Serengeti: Lessons for Conservation - A.R.E. SINCLAIR; SIMON A.R. MDUMA; J. GRANT C. HOPCRAFT; JOHN M. FRYXELL; RAY HILBORN; SIMON THIRGOOD (Conservation Biology, 2007)
Data from long‐term ecological studies further understanding of ecosystem dynamics and can guide evidence‐based management. In a quasi‐natural experiment we examined long‐term monitoring data on different components of the Serengeti‐Mara Ecosystem to trace the effects of disturbances and thus to elucidate cause‐and‐effect connections between them. The long‐term data illustrated the role of food limitation in population regulation in mammals, particularly in migratory wildebeest and nonmigratory buffalo. Predation limited populations of smaller resident ungulates and small carnivores. Abiotic events, such as droughts and floods, created disturbances that affected survivorship of ungulates and birds. Such disturbances showed feedbacks between biotic and abiotic realms. Interactions between elephants and their food allowed savanna and grassland communities to co‐occur. With increased woodland vegetation, predators' capture of prey increased. Anthropogenic disturbances had direct (hunting) and indirect (transfer of disease to wildlife) effects. Slow and rapid changes and multiple ecosystem states became apparent only over several decades and involved events at different spatial scales. Conservation efforts should accommodate both infrequent and unpredictable events and long‐term trends. Management should plan on the time scale of those events and should not aim to maintain the status quo. Systems can be self‐regulating through food availability and predator‐prey interactions; thus, culling may not be required. Ecosystems can occur in multiple states; thus, there may be no a priori need to maintain one natural state. Finally, conservation efforts outside protected areas must distinguish between natural change and direct human‐induced change. Protected areas can act as ecological baselines in which human‐induced change is kept to a minimum

Diversity of Glomale Mycorrhizal Fungi in Maize/Sesbania Intercrops and Maize Monocrop Systems in Southern Malawi - Joyce M. Jefwa; Robert Sinclair; Jumanne A. Maghembe (Agroforestry Systems, 2006)

Consequences of Transferring Three Sorghum Genes for Secondary Metabolite (Cyanogenic Glucoside) Biosynthesis to Grapevine Hairy Roots - T. K. Franks; K. S. Powell; S. Choimes; E. Marsh; P. Iocco; B. J. Sinclair; C. M. Ford; R. van Heeswijck (Transgenic Research, 2006)

Do patterns of Steller sea lion ( Eumetopias jubatus ) diet, population trend and cetacean occurrence reflect oceanographic domains from the Alaska Peninsula to the central Aleutian Islands? - ELIZABETH H. SINCLAIR; SUE E. MOORE; NANCY A. FRIDAY; TONYA K. ZEPPELIN; JANICE M. WAITE (Fisheries Oceanography, 2005)
Shipboard surveys were conducted along the Aleutian Islands in 2001 and 2002 to assess the influence of a suite of biophysical parameters on regional patterns in the distribution of cetaceans and Steller sea lions (SSL; Eumetopias jubatus ). Distributions of four large whale species: fin ( Balaenoptera physalus ), humpback ( Megaptera novaeangliae ), minke ( B. acutorostrata ) and sperm ( Physeter macrocephalus ) aligned with proposed metapopulation breaks in diet and population trend of SSLs. Dall's porpoise ( Phocoenoides dalli ) and killer whales ( Orcinus orca ) were widely distributed throughout the study area, and killer whales were particularly prevalent along the north Aleutian Island coastlines between Unimak Pass and Samalga Pass. Biopsies determined that most killer whales (92%) were of the piscivorous (resident) ecotype as opposed to the mammal‐eating (transient) ecotype observed in 2002 only. Generalized additive models (GAMs) were used to explore relationships between these multispecies patterns in distribution, oceanographic variables (salinity, temperature, fluorescence and depth) and proximity to six Aleutian passes. The GAMs indicated the best‐fit models and most significant correlations as determined by the Akaike function and Cp‐statistics were: depth and proximity to the nearest measured pass for SSLs and all cetaceans, respectively; frequencies of herring and salmon in SSL diet with population trend; fluorescence in the top 50 m with occurrence of humpback, minke, and killer whales; and surface temperature with occurrence of humpback, killer, and sperm whales. Results of the GAM analyses suggest foci for future investigation of relationships between physical variables and interspecific patterns of marine mammal distribution.

Landscape scale, heterogeneity, and the viability of Serengeti grazers - John M. Fryxell; John F. Wilmshurst; Anthony R. E. Sinclair; Daniel T. Haydon; Robert D. Holt; Peter A. Abrams (Ecology Letters, 2005)
Species persistence can be threatened by substantial temporal variation in food resources over time. On the other hand, spatial heterogeneity in resources at the landscape scale might allow mobile consumers to compensate for temporal variability in resource availability at the local scale. We evaluated this hypothesis, using an extensive data set on foraging, grass growth, and movement by Thomson's gazelles living on the Serengeti Plains. Here we show that modelled populations of Thomson's gazelles can only persist under Serengeti conditions in the face of observed levels of rainfall stochasticity by making adaptive movements to take advantage of ephemeral spatial distributions of food resources. More importantly, our models suggest that Thomson's gazelles in Serengeti require unrestricted access to relatively large areas of grassland (> 1600 km 2 ) to guarantee long‐term persistence, particularly when there is positive spatial autocorrelation in resource abundance, as is the case in Serengeti. If this proves to be true for other species and/or other systems, then understanding of complex behavioural responses to spatially and temporally heterogeneous food supplies may be essential to successful conservation of grazing herbivores.

Species distributions, surrogacy, and important conservation regions in Canada - Leanna D. Warman; David M. Forsyth; A. R. E. Sinclair; Kathryn Freemark; Harold D. Moore; Thomas W. Barrett; R. L. Pressey; Denis White (Ecology Letters, 2004)
Conservation actions could be more efficient if there is congruence among taxa in the distribution of species. Patterns in the geographical distribution of five taxa were used to identify nationally important regions for conservation in Canada. Two measures of surrogacy were significantly and positively correlated among taxa, and conservation areas selected for one taxon represented other taxa significantly better than random selections. However, few large protected areas exist in the sites of highest conservation value in southern Canada; these regions are therefore a priority for future conservation regard. By focusing this effort on threatened and endangered species, which are a national priority in Canada, most other species could also benefit.

A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - R. A. Sharrock; F. L. Sinclair; C. Gliddon; I. M. Rao; E. Barrios; P. J. Mustonen; P. Smithson; D. L. Jones; D. L. Godbold (Mycorrhiza, 2004)

Regulation of glucose utilization and lipogenesis in adipose tissue of diabetic and fat fed animals: Effects of insulin and manganese - Najma Z. Baquer; M. Sinclair; S. Kunjara; Umesh C. S. Yadav; P. McLean (Journal of Biosciences, 2003)

Tree and livestock productivity in relation to tree planting configuration in a silvopastoral system in North Wales, UK - Z. Teklehaimanot; M. Jones; F.L. Sinclair (Agroforestry Systems, 2002)

Evolutionary relationships of the New Caledonian heterotrophic conifer, Parasitaxus usta (Podocarpaceae), inferred from chloroplast trn L-F intron/spacer and nuclear rDNA ITS2 sequences - W.T. Sinclair; R.R. Mill; M.F. Gardner; P. Woltz; T. Jaffré; J. Preston; M.L. Hollingsworth; A. Ponge; M. Möller (Plant Systematics and Evolution, 2002)

Detecting a genetic bottleneck in Gilbert's Potoroo (Potorous gilbertii) (Marsupialia: Potoroidae), inferred from microsatellite and mitochondrial DNA sequence data - Elizabeth A. Sinclair; Brian Costello; Jacqueline M. Courtenay; Keith A. Crandall (Conservation Genetics, 2002)

On-farm evaluation of the establishment of clonal rubber in multistrata agroforests in Jambi, Indonesia - S. E. Williams; M. van Noordwijk; E. Penot; J. R. Healey; F. L. Sinclair; G. Wibawa (Agroforestry Systems, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Control of Fusarium head blight of wheat with fungicides - M. G. Cromey; D. R. Lauren; R. A. Parkes; K. I. Sinclair; S. C. Shorter; A. R. Wallace (Australasian Plant Pathology, 2001)

Regional Patterns of Streamwater Acidity and Catchment Afforestation in Galloway, SW Scotland - Christoph B. Puhr; Daniel N. M. Donoghue; Alastair B. Stephen; David J. Tervet; Callum Sinclair (Water, Air, & Soil Pollution, 2000)

Cod and haddock spawning on Georges Bank in relation to water residence times - F. H. Page; M. Sinclair; C. E. Naimie; J. W. Loder; R. J. Losier; P. L. Berrien; R. G. Lough (Fisheries Oceanography, 1999)
The seasonal and geographical patterns of spawning for Georges Bank cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are estimated using composite distributions of stage I eggs derived from the Marine Resources Monitoring, Assessment and Prediction (MARMAP) data set (1977–1987). The inferred mean spawning locations are compared with patterns in particle residence times derived from a three‐dimensional prognostic circulation model that estimates the tidal and seasonal mean circulation. The comparisons indicate that cod and haddock spawning occurs at times and locations characterized by model residence times in excess of 35 d. The results are discussed in the context of fish population regulation theory, particularly the member/vagrant hypothesis and the concept of abundance‐dependent vagrancy.

Effect of tree species and crown pruning on root length and soil water content in semi-arid agroforestry - M. Jones; F.L. Sinclair; V.L. Grime (Plant and Soil, 1998)

Sensitivity of Wild Cotton Rats ( Sigmodon hispidus ) to the Immunotoxic Effects of Low-Level Arsenic Exposure - M. Savabieasfahani; R. L. Lochmiller; D. P. Rafferty; J. A. Sinclair (Archives of Environmental Contamination and Toxicology, 1998)

Secondary poisoning of birds of prey by the organophosphorus insecticide, phorate - John E. Elliott; Laurie K. Wilson; Ken M. Langelier; Pierre Mineau; Pamela H. Sinclair (Ecotoxicology, 1997)

Estimating long-term annual precipitation in a mountainous region from a diagnostic model - C. S. Thompson; M. R. Sinclair; W. R. Gray (International Journal of Climatology, 1997)

Regeneration of transgenic vegetable brassicas (Brassica oleracea and B. campestris) via Ri-mediated transformation - M. C. Christey; B. K. Sinclair; R. H. Braun; L. Wyke (Plant Cell Reports, 1997)

Regeneration of transgenic vegetable brassicas (Brassica oleracea andB. campestris) via Ri-mediated transformation - M. C. Christey; B. K. Sinclair; R. H. Braun; L. Wyke (Plant Cell Reports, 1997)